JavaScript Interview Preparation Practice Problems - Traub, Eric (Packt Publishing, 2020)
Succeed in your next JavaScript coding interview by working through practice questions and learning important JavaScript skills and concepts About This Video Learn the concepts and techniques that interviewers usually test candidates on in JavaScript programming interviews Gain insights into the actual format of programming interviews In Detail This course is designed to help you prepare effectively for any JavaScript programming interview. Since programming interviews require intense preparation, with practice being the key to succeeding, this course will ensure you are well-equipped to make an impression. In this course, you will complete more than 30 JavaScript interview questions that come from actual JavaScript interviews. You will understand how to approach problems, solve each one, and use the best solution to each problem in a step-by-step manner. You'll also delve into the skills, concepts, and techniques that are required to solve each problem. All along, the course helps you strengthen your JavaScript programming skills and knowledge of fundamental concepts through a hands-on style. The course covers a mix of ES5 and ES6 code to ensure that you grasp the fundamental concepts effectively. By the end of this course, you will be well-versed with more than 30 interview questions, and have the skills and techniques you need to know to succeed in interviews.